2016
DOI: 10.1039/c6ra15477h
|View full text |Cite
|
Sign up to set email alerts
|

Low variability of single-molecule conductance assisted by bulky metal–molecule contacts

Abstract: A detailed study of the trimethylsilylethynyl moiety, –CCSiMe3 (TMSE), as an anchoring group, using a combination of experiment and DFT is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 52 publications
4
18
0
Order By: Relevance
“…14,[95][96][97] This is due to the fact that the CuCSiMe 3 group makes effective electrical contact to defect sites on the gold electrode surfaces in a restricted range of geometries, limited in part due to the steric bulk of the ancillary methyl groups. 67 Thus, in even π-rich oligophenylene ethynylene based molecules, the large footprint and limited range of conducting configurations that are available to CuCSiMe 3 contacts gives rise to conductance histograms featuring only a single conductance peak without complications from alternative conductive molecular orientations or contacts within the junction 14,14,67,96 As will be seen in the discussion that follows, the relatively weak nature of the CuCSiMe 3 -gold interaction (estimated at ca. 0.4-0.7 eV) 14,67 permits competitive, if adventitious, interactions between the STM tip and other regions of the molecule.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…14,[95][96][97] This is due to the fact that the CuCSiMe 3 group makes effective electrical contact to defect sites on the gold electrode surfaces in a restricted range of geometries, limited in part due to the steric bulk of the ancillary methyl groups. 67 Thus, in even π-rich oligophenylene ethynylene based molecules, the large footprint and limited range of conducting configurations that are available to CuCSiMe 3 contacts gives rise to conductance histograms featuring only a single conductance peak without complications from alternative conductive molecular orientations or contacts within the junction 14,14,67,96 As will be seen in the discussion that follows, the relatively weak nature of the CuCSiMe 3 -gold interaction (estimated at ca. 0.4-0.7 eV) 14,67 permits competitive, if adventitious, interactions between the STM tip and other regions of the molecule.…”
Section: Resultsmentioning
confidence: 99%
“…14,67 It is only these latter situations that give rise to CuCSiMe 3 -contacted junctions of sufficient conductance to be measured. However, the potential for molecules to bind in a number of distinct configurations within a molecular junction, each offering a distinct contact and hence conductance value, has been recognized.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, it was shown that conductance histograms generated from trans-[Ru(C≡CC 6 H 4 -4-C≡CSiMe 3 ) 2 (dppe) 2 ] and Me 3 SiC≡CC 6 H 4 -4-C≡CC 6 H 4 -4-C≡CC 6 H 4 -4-C≡CSiMe 3 , by the I(s) method [24] were simplified in comparison with the thiolatecontacted compounds, with trimethylsilylethynyl binding groups giving only a single, narrow conductance peak as the steric bulk of the termini restricts the range of available, conductive contacts. [25] A higher conductance value was again obtained for the organometallic complex (5.10 ± 0.99 10 -5 G 0 ) compared with the organic analogue. [26] Efforts are now being expended on the preparation and measurement of longer, multi-metallic organometallic wires of ruthenium [27][28][29] and other metals [30][31][32] which have clearly demonstrated the potential for organometallic compounds of this trans-bis(alkynyl) type to find application in molecular electronic platforms.…”
Section: Introductionmentioning
confidence: 81%